Mollusks (Gastropoda and Bivalvia) of the multiple-use reserve martín garcía Island, Río de la plata river: biodiversity and ecology - César, Inés Irma (2012)
The Island of Martin Garcia is located in the Upper Río de la Plata, to the south of mouth the Uruguay River. The aim of the present study was to analyse the biodiversity of the island freshwater mollusks and their relationships to environmental variables. Twelve sampling sites were selected, five were along the littoral section of the island and seven were Inland ponds. Seven major environmental variables were measured: water and air temperature, percentage of oxygen saturation, dissolved oxygen, electrical conductivity, total dissolved solids and pH. Twenty-seven mollusk species were found, Antillorbis nordestensis, Biomphalaria tenagophila tenagophila, B. t. guaibensis, B. straminea, B. peregrina, Drepanotrema kermatoides, D. cimex, D. depressissimum, Chilina fluminea, C. rushii, C. megastoma, Uncancylus concentricus, Hebetancylus moricandi, Stenophysa marmorata, Heleobia piscium, H. parchappii, Potamolithus agapetus, P. buschii, P. lapidum, Pomacea canaliculata, P. megastoma Asolene platae, Corbicula fluminea, Eupera platensis, Pisidium sterkianum, P. taraguyense and Limnoperna fortunei. UPGMA clustering of species based on their occurrence in different ecological conditions revealed two main species groups. The Canonical Correspondence Analysis suggests that the species distribution is related to the physico-chemical condition of water. Axis two of the ordination diagram displayed the approximately 95.6% of the correlation between species and environmental variables. Dissolved oxygen, conductivity, water temperature and pH showed the highest fluctuations during the sampling period. The species richness (S) showed relationships mainly with water temperature and conductivity. The biodiversity of the gastropods and bivalves from Martín García Island amounts to up to 26 species. Among the Gastropoda, the Planorbidae family made the most sizeable contribution. The Lithogliphidae P. agapetus (26.28%) and P. buschii (9.50%) showed the highest relative frequencies of occurrence within the littoral environments, while the Planorbidae D. cimex (23.83%) and D. kermatoides (11.59%) likewise did so in the inland ponds.